Pemanfaatan Teknologi Informasi dalam Pelayanan Hukum di Pengadilan Indonesia - Dwi Wahyu Endarto; Achmad Nasyruddin; Bayu Adhy Nugraha; Jueni Jueni; Ikbal Ikbal; Firman Adi Candra (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
The development of information technology has significantly influenced the Indonesian judicial system. Courts have implemented digital services to improve efficiency, transparency, and public access to justice. Electronic court systems, online case registration, and digital hearings are examples of legal technology implementation in Indonesia. This study aims to analyze the utilization of information technology in legal services within Indonesian courts. The research uses a normative juridical method through statutory and conceptual approaches. The findings indicate that information technology has improved judicial administration and accelerated legal processes. However, challenges remain regarding digital infrastructure, cybersecurity, and public understanding of electronic legal services. The study concludes that strengthening digital infrastructure and legal literacy is necessary to optimize technology-based legal services in Indonesia.